2017
DOI: 10.5301/jva.5000762
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life of Cancer Patients with Peripherally Inserted Central Catheter: A Pilot Study

Abstract: HRQOL varies in different types of cancer patients with PICC. PICC may have a low impact on cancer patients' HRQOL. Further large sample studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…A systematic review of the risk factors for CRBSIs in patients receiving HPN has showed that a family caregiver or a nurse aid is not associated to an increase of infection risk, if compared with complete autonomy; on the contrary, self‐management of the VAD is associated with an increased risk of CRBSIs compared with management by family caregiver or nurse 41 . Kang et al reported that the limitation of the upper extremity activity was absent or minimal in 94% of cancer patients with PICCs 42 . Molloy et al found that most cancer patients held favorable views toward having a PICC and could adapt well to PICCs with minimal changes of daily living activities, so they would recommend a PICC to other patients 43 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of the risk factors for CRBSIs in patients receiving HPN has showed that a family caregiver or a nurse aid is not associated to an increase of infection risk, if compared with complete autonomy; on the contrary, self‐management of the VAD is associated with an increased risk of CRBSIs compared with management by family caregiver or nurse 41 . Kang et al reported that the limitation of the upper extremity activity was absent or minimal in 94% of cancer patients with PICCs 42 . Molloy et al found that most cancer patients held favorable views toward having a PICC and could adapt well to PICCs with minimal changes of daily living activities, so they would recommend a PICC to other patients 43 …”
Section: Discussionmentioning
confidence: 99%
“…CICC reported that the limitation of the upper extremity activity was absent or minimal in 94% of cancer patients with PICCs. 42 Molloy et al found that most cancer patients held favorable views toward having a PICC and could adapt well to PICCs with minimal changes of daily living activities, so they would recommend a PICC to other patients. 43 One of the differences of HPN in patients with benign underlying disease vs cancer patients is the duration of HPN, which will be notably shorter (months vs years) in the latter.…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al published a pilot study in 2017 involving 357 patients with different cancer forms treated via a PICC. 126 The authors concluded that quality-of-life measures vary according to the type of cancer and that a PICC probably has a low impact on overall quality-of-life. In another small Italian study describing patients receiving palliative home-care, PICCs appeared to cause little pain and distress.…”
Section: Patient Perceptionmentioning
confidence: 99%
“…Adjuvant chemotherapy stands as a primary treatment strategy for BC in clinical practice, with intravenous infusion via a peripherally inserted central catheter (PICC) increasingly serving as the primary method for long-term administration of chemotherapeutic agents and parenteral nutrition [ 2 ]. Nevertheless, the extended use of PICC insertion for delivering chemotherapeutic drugs has been linked to various psychological burdens in cancer patients [ 3 ], with cancer-related fatigue (CRF) and cancer-related uncertainty being deemed the primary adverse outcomes of chemotherapy for BC patients [ 4 ].…”
Section: Introductionmentioning
confidence: 99%